Training on Preparation of Electronic-Based Teaching Materials for Teachers in Muara Gembong District, Bekasi Regency, West Java - Arris Maulana; Shilmi Arifah; Arief Saefudin; Riyan Arthur; Adila Joya Puspita; Firros Hirzy (Publikasi Pendidikan, 2023)
The development of science and technology is growing rapidly in the world of education. Thus, the government and educational institutions in Indonesia have increased the development of teaching materials, through increasing teacher professionalism in making interesting, creative and innovative teaching materials aimed at improving the quality of teaching materials using technology in the form of electronic devices such as computers, tablets and smartphones. The purpose of this research is to provide guidance to the teachers of SMA Negeri 1 Muara Gembong regarding the preparation of teaching materials for teachers according to the subjects taught by utilizing technology, namely the Canva media design. The method used in carrying out this mentoring activity is varied lectures, direct practice of developing teaching materials, and mentoring the application of teaching materials that have been made in learning. The population in this study were teachers at SMA Negeri 1 Muara Gembong with a total sample of 25 participants or 25 teachers from various subjects taught. The training took place in one of the Muara Gembong 1 Public High School classes for approximately one day. The instrument used in this study was a questionnaire in the form of a survey of participants' satisfaction with the material that had been given by the speaker and presented. So, the results obtained were that the material presented was very useful and the participants wanted to hold another training on the preparation of electronic-based teaching materials because it was very useful for the teachers of SMA Negeri 1 Muara Gembong.